2007
DOI: 10.1108/02651330710755311
|View full text |Cite
|
Sign up to set email alerts
|

Global brand communities across borders: the Warhammer case

Abstract: PurposeThe “brand community” concept believes that the meaning of the brand transcends national boundaries. However, such an assumption presents challenges arising out of several reasons including co‐existence of sub‐tribes within a given brand community that allocate different meanings to a particular brand. This plurality of meanings seems exacerbated for global brands where meanings are shaped by tremendously varying cultures. Aims to address the issues.Design/methodology/approachThis text relies on a compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
70
0
5

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 118 publications
(80 citation statements)
references
References 25 publications
2
70
0
5
Order By: Relevance
“…In line with other OBC studies, the sampling sought highly engaged consumer informants (Cova, Pace, & Park, 2007;Muñiz & Schau, 2005) of diverse demographic profiles. Consumers were asked to select one or several brands that they followed on OBCs embedded in social networks and to explain their interactions with other consumers and brands in these settings.…”
Section: Study 1: Dimensionality Of Consumer Engagement and Item Genementioning
confidence: 99%
“…In line with other OBC studies, the sampling sought highly engaged consumer informants (Cova, Pace, & Park, 2007;Muñiz & Schau, 2005) of diverse demographic profiles. Consumers were asked to select one or several brands that they followed on OBCs embedded in social networks and to explain their interactions with other consumers and brands in these settings.…”
Section: Study 1: Dimensionality Of Consumer Engagement and Item Genementioning
confidence: 99%
“…However, a re-investigation of some of the consumer interviews in certain situations of co-creation, such as the posting of narratives and pictures on the Nutella website (Cova and Pace, 2006) and producing rules and tournaments for the war game Warhammer (Cova, Pace and Park, 2007), reveals a kind of double movement. During a first phase, the productive consumer enjoys co-creating and is generally (very) pleased to see his/her production being recognised by the company and other consumers.…”
Section: (2008)mentioning
confidence: 99%
“…Scholars have also begun to focus on the online brand community experience. Cova [7] found that when the experience is consistent with consumers' expectations, they tend to face brand marketing activities with a positive attitude. It is obvious that community experience has some effect on consumer thinking and behavior.…”
Section: Theoretical Background and Research Hypothesis Online Brand mentioning
confidence: 94%